In silico structural and functional analysis of human calcium binding protein-5 (CaBP5) - JITENDER SINGH; ASHVINDER RAINA (International Journal of Pharma and Bio Sciences, 2017)
Studies showing the role of Ca2+-binding proteins (CaBPs) in mammalian retinal neurons has yielded new insights into the function of these proteins in normal and abnormal states. CaBP5 is a neuronal calmodulin-like Ca2âº-binding protein that is expressed in the cochlea and retina. Although CaBP5 knockout mice displayed reduced sensitivity of retinal ganglion cell light responses, the exact 3D structure and function of CaBP5 is still unknown. To gain further insight into CaBP5 structure and function, we tried in silico structural and functional analysis of CaBP5. In this study, human Ca2âº-binding protein (CaBP-5) having 173 amino acid residues was retrieved from NCBI (Accession no AAF25793.1) and analysed for the structural and functional characteristics using various bioinformatic tools and databases. The analysis revealed structurally and functionally important domains and families and protein-protein interacting partners as PPP3R1, GRK5, MYO5A, MYO5B, MYO5C, OBSCN, MYO1G, RAB30, POTEF and POTEE which might have a role in disease. The structural and binding site prediction of this protein has been done with an aim that it would be useful in docking studies for aiding in the drug discovery.